SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP LENOVO IDEAPAD DI TOKOPEDIA MENGGUNAKAN METODE TOPSIS - Dian Kinasih, Intan Ratu; Sari, Renny Puspita (Jurnal Ilmiah Sistem Informasi, 2024)
Laptop is one of the important objects needed by the general public to facilitate productivity such as educational activities and work activities. Laptops are portable computer devices used by humans, especially students, to significantly increase educational productivity through education-based software. Even so, to buy a laptop that suits your needs is sometimes a difficult thing because in this era there are many laptop brands with high specifications and varying prices. A Decision Support System (DSS) is a tool used to assist decision making by a decision maker. Decisions generated by SPK are usually fast and quantitatively the best choice based on the weight of the criteria given by management. With SPK, complex decision-making processes can be completed more efficiently. The TOPSIS method is a multicriteria decision-making technique based on the principle that the best alternative is the one that has the closest distance to the positive ideal solution and at the same time has the greatest distance from the negative ideal solution. With the TOPSIS method, it is expected that the assessment will be more accurate because it is based on predetermined criteria values and weights. The benefit of this research is the creation of an application website that can facilitate users in choosing Lenovo laptop devices on Tokopedia e-commerce that suit their needs. The results showed that calculations using the TOPSIS method carried out in Excel and those in the system had the same results, so the website created had been successfully implemented in accordance with the TOPSIS formula. The results of this research show that the laptop that gets the 1st rank is the Lenovo IdeaPad Pro 5 14IMH9 laptop with a value of 1, ranked 2 Lenovo IdeaPad Slim 3 14IRH8 with a value of 0.7468, ranked 3 Lenovo IdeaPad Slim 5 14IRL8 with a value of 0, 6788, ranked 4 Lenovo IdeaPad Duet 5i 12IRU8 with a value of 0.5784, ranked 5 Lenovo IdeaPad Slim3i 14IAU7 with a value of 0.4235, and ranked 6 is Lenovo IdeaPad Slim 1 14IGL7 with a value of 0.3229.